EPIDEMIOLOGY OF AGE-DEPENDENCE IN SLEEP DISORDERED BREATHING (SDB) IN OLD AGE: THE BAY AREA SLEEP COHORT (BASC) - Bliwise, Donald L. (2009)
Sleep Disordered Breathing (SDB) is highly prevalent in elderly populations and is thought to reflect, at least in part, age-dependence. Several studies suggest that SDB in elderly populations may hold different functional outcomes relative to SDB in middle-aged populations. Risk factors for SDB specific for the elderly remain uncertain. In this report, we examined changes in SDB, body weight and pulmonary function in 103 individuals over an average interval of 7 years to determine whether changes in these measures covaried. In-lab polysomnography was performed on members of an elderly cohort (Bay Area Sleep Cohort) on two separate occasions (Time 1, Time 2) with multiple nights of measurement typically made on each occasion. Results indicated that: a) SDB progressed over time in both men and women; b) changes in body weight were unrelated to the progression in SDB; c) relative declines in lung volumes (Forced Vital Capacity, Forced Expiratory Volume in 1.0 second) were associated with relative increases in SDB, with the effects slightly stronger in men. These data suggest that age-dependence in one commonly ascribed aging biomarker (lung function) were coupled to increments in SDB. Maintenance of healthy lung function into old age may confer some protective benefits in the development of age-dependent SDB.